Hernial appendicitis - Valls, Alberto; di Leoni, Francisco J (Cirugía del Uruguay, 1975)
Comments are made on acute hernial appendicitis. It is mentioned that, normally, diagnosis is strangulated hernia, although in this particular case mention should be made .of the scarce general repercussion and frequent absence or very slight variance in fever. The surgical approach, when the appendix is whole in the sac, is appendectomy through the hernial sac. If the base is within the abdomen, the approach must be through the abdomen so as to secure the base f the appendix, removing it immediately through the hernia! sac. If it is an hernia! appendicular peritonitis, the sac is drained and the visceral content is not reduced within the abdomen, leaving the hernia treatment for a future instance.